2015
DOI: 10.1159/000367689
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Objective SCORAD and Three-Item Severity Score Used by Physicians and Objective PO-SCORAD Used by Parents/Patients in Children with Atopic Dermatitis

Abstract: Background: A self-assessment rating scale (SAS) is a good tool to assess the fluctuating disease severity and quality of life (QoL) in children with atopic dermatitis (AD). The European Task Force on Atopic Dermatitis created an SAS based on the Scoring Atopic Dermatitis (SCORAD) index, called the Patient-Oriented SCORAD (PO-SCORAD). Objective: The aim of our study was to measure the correlation between alternative systems such as the Objective SCORAD, the Three-Item Severity (TIS) score and the Objective PO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
4
9
1
Order By: Relevance
“…who proposed a new self‐assessment tool, evaluating the burden of AD before and after treatment, which showed promise by being correlated with disease severity. The similar correlations between self‐reported and healthcare professional‐assessed measures of disease activity found in our study supports the suggestion by Oosterhout et al . comparing SCORAD to PO‐SCORAD, reporting a positive correlation ( r = 0.63, P < 0.001), as well as Baron et al .…”
Section: Discussionsupporting
confidence: 92%
“…who proposed a new self‐assessment tool, evaluating the burden of AD before and after treatment, which showed promise by being correlated with disease severity. The similar correlations between self‐reported and healthcare professional‐assessed measures of disease activity found in our study supports the suggestion by Oosterhout et al . comparing SCORAD to PO‐SCORAD, reporting a positive correlation ( r = 0.63, P < 0.001), as well as Baron et al .…”
Section: Discussionsupporting
confidence: 92%
“…3b). However, the appraisement of the symptom sleeplessness by the parents differs between PO-SCORAD and SCORAD in the present study [22]. The sleeplessness score was significantly reduced (fig.…”
Section: Discussioncontrasting
confidence: 53%
“…The Patient-Oriented SCORing Atopic Dermatitis (PO-SCORAD) represents a self-assessment score to involve parents in effective skin monitoring [13,18]. Sharing a comparable analytic factor as the SCORAD, the PO-SCORAD facilitates the communication between parents and physicians [19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…The severity of AD was assessed both by the physician and by the participant and there were no significant differences at the first examination either in the intervention or in the control group. Previous studies have shown that assessments of disease severity both by the physician and by the participants (caregivers) tend to be similar …”
Section: Discussionmentioning
confidence: 99%